A STATE OF MIND: DOMINATION, COERCION AND ABUSE IN THE SOUTH AFRICAN MENTAL HEALTH CARE ACT - Davis, Sam (PINS-Psychology in Society, 2026)
This paper examines the South African Mental Health Care Act, focussing on its ideological and theoretical underpinnings. It argues that the Act is flawed not only through clear textual inconsistencies, but further, as a consequence of its view of mental illness resting on contestable psychiatric dogma. Specifically, the disease model of mental illness reproduced in the policy allows the desires, thoughts and behaviours of psychiatric patients to be entirely delegitimised, and replaced with the arbitrary system favoured by the psychiatric institution. It will further be argued that it is the very power of the legislative-psychiatric complex that allows the codes of conduct prescribed by the discipline of psychiatry lo be accepted as an objectively normative way of being, further masking the tenuous nature of the truth claims psychiatry makes about human cognition and behaviour.